2018
DOI: 10.5993/ajhb.42.6.4
|View full text |Cite
|
Sign up to set email alerts
|

Act-Belong-Commit Indicators Promote Mental Health and Wellbeing among Irish Older Adults

Abstract: Objective Act-Belong-Commit is the world's first population-wide, community-based mental health promotion campaign. We assessed the associations between baseline indicators of Act-Belong-Commit behavioral domains and wellbeing at 2-year follow-up in a population-based sample of Irish older adults. MethodsData from 2 waves of the Irish Longitudinal Study on Ageing were analyzed. The sample consisted of 6098 adults. Outcomes were quality of life (QoL), life satisfaction (LS) and self-rated mental health (SRMH). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 89 publications
3
16
0
Order By: Relevance
“…Nonetheless, the results of our study have depicted a robust picture regarding the structures of clinically depressed individuals' confidant networks. Agreeing with previous findings on the importance of larger social network size and wide compositions (diverse group members) in confronting depression [2,58], we also found other important structural features of networks matter. Indeed, our study suggested the importance of a network structure suggesting active confidant seeking (shown by low constraint) and that may be an important indicator of positive depression mitigating behavior processes and outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…Nonetheless, the results of our study have depicted a robust picture regarding the structures of clinically depressed individuals' confidant networks. Agreeing with previous findings on the importance of larger social network size and wide compositions (diverse group members) in confronting depression [2,58], we also found other important structural features of networks matter. Indeed, our study suggested the importance of a network structure suggesting active confidant seeking (shown by low constraint) and that may be an important indicator of positive depression mitigating behavior processes and outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…The ABCs partnership has been granted funding for three project phases: 2014-2016, 2016-2018 and 2018-2021. Further information on the background and organisation of the ABCs can be found elsewhere [9,10,[18][19][20]22,23].…”
Section: Organisation Of the Abcs Of Mental Healthmentioning
confidence: 99%
“…The three domains are derived from primary research on lay peoples understandings of mental health promoting behaviour and reviewing the scientific literature [ 10 ]. Recent longitudinal population-based studies have demonstrated the mental health promoting effects of the factors pertaining to these domains have [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is critical to prevent adverse health outcomes in the adolescent population by the promotion of behaviors known to promote mental health through (1) active lifestyles, (2) social connectedness, and (3) meaningful commitment or contribution to society. While there is a multitude of behavioral factors that may benefit mental health, a number of studies have shown that these three behavioral domains-known as Act-Belong-Commit-promote positive mental health in adulthood as well as protect against mental, neurological, and alcohol use disorders (Nielsen et al, 2017;Santini et al, 2017aSantini et al, , 2018a. Act-Belong-Commit, also referred to as the ABCs of Mental Health, is a mental health campaign and framework for doing mental health promotion, which is currently being deployed in different parts of the world (Koushede et al, 2015;Santini et al, 2018).…”
Section: Implications For Policy and Practicementioning
confidence: 99%
“…Engagement in leisure activities is generally considered an indicator of relational health and social well-being, since such activities often promote or reinforce shared interests among adolescents and their peers, as well as social interaction during these activities (Zeijl et al, 2000;Caldwell and Faulk, 2013). Research suggests that engaging in leisure activities-particularly those that require effort, concentration, or commitment-is essential in the protection and promotion of good mental health (Trainor et al, 2010;Santini et al, 2017aSantini et al, , 2018a. This is also supported in research on adolescents as well as school-based interventions (Bartko and Eccles, 2003;Palen and Coatsworth, 2007;Trainor et al, 2010;Anwar McHenry et al, 2018).…”
Section: Introductionmentioning
confidence: 99%